English as a Foreign Language for Students of Stakn Kupang: A Study of Learners’ Needs - Junaity Soften Sine; Desty A. Bekuliu; Mardolitha Loak (Universitas Pendidikan Mandalika, 2021)
The process in identifying the situation analysis of a target language is called Needs Analysis or Needs Assessment (NA). To be effective and efficient in learning process in English classroom at STAKN Kupang, this analysis is considered important. NA is divided into two parts of analysis namely present situation analysis and target situation analysis. A quantitative approach was used in this research with a survey method. The findings show: 1) In general, the English proficiency of the students of Study Program Christian Religious Education in academic year 2018-2019 was beginner (basic); 2) There were several reasons why they stopped learning English such as the materials used were not applicable on daily basis, their teachers did not use good teaching method, or the materials was not interesting and challenging; 3) Students thought that learning grammar and the differences between Bahasa Indonesia and English is important to be covered in textbooks; 4) Students preferred their teachers to explain the grammatical theories before giving them practice activities; 5) Even though students admitted that English is a difficult language, they agreed that English is very important to be mastered and it has become a language widely used for international occasions.